Analysis and Optimal Control in the Cancer Treatment Model with Combining Radio and Anti-angiogenic Therapy - Nastitie Nastitie; Didik Khusnul Arif ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2017)
Cancer is a disease characterized by uncontrolled cell division and the ability of these cells to invade other tissues, either tissue next to them or not. Cancer treatment process is very diverse. The issue in this paper is about the treatment of cancer that processed by combining radio and anti-angiogenic therapy, which is intended to minimize the size of cancer, by adding control w (dose of radiotherapy) and u (dose of antiangiogenic). By applying Pontryagin minimum principle, the simulation results show that the size of the cancer become the most minimum if given minimum weight of anti-angiogenic (P) therapy is 0.3 and radiotherapy (Q) is 0.015. Which take big effect of this treatment is dose of anti-angiogenic therapy.